2023
DOI: 10.1108/caer-03-2021-0062
|View full text |Cite
|
Sign up to set email alerts
|

Health vulnerability and health poverty of rice farmers: evidence from Hubei province in China

Abstract: PurposeThe purpose of this study was threefold: (1) to measure farmers' health poverty, (2) to examine the effect of health vulnerability on health poverty and (3) to identify countermeasures that may alleviate health poverty in rural China.Design/methodology/approachThis study built a health poverty measurement model based on the multi-dimensional poverty framework to evaluate farmers' health vulnerability. Further, this paper used an econometric model to assess the impact of health vulnerability on health po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…The elasticities of physical capital, land, and labor in the maize production function are 0.377, 0.496, and 0.026, respectively, which are highly consistent with the characteristics of resource endowment for maize production in China. Land is the most rare element in maize production, capital plays an equally important role, and only labor is affluent (Li et al, 2010). The sum of the three coefficients is 0.899, indicating that maize production is diminishing returns to scale, which is consistent with the findings of Chari et al (2021).…”
Section: Measurement Results Of Mtfp In Chinasupporting
confidence: 74%
See 1 more Smart Citation
“…The elasticities of physical capital, land, and labor in the maize production function are 0.377, 0.496, and 0.026, respectively, which are highly consistent with the characteristics of resource endowment for maize production in China. Land is the most rare element in maize production, capital plays an equally important role, and only labor is affluent (Li et al, 2010). The sum of the three coefficients is 0.899, indicating that maize production is diminishing returns to scale, which is consistent with the findings of Chari et al (2021).…”
Section: Measurement Results Of Mtfp In Chinasupporting
confidence: 74%
“…Referring to existing studies (Wu et al, 2005;Li et al, 2010;Gao et al, 2017), this paper controls for other influencing factors affecting maize productivity. They are as follows: (1) Sex of household (Gender), male is 1, female is 0; (2) Age of household (Age), expressed as the age of the head of the respondent's household in weeks; (3) Educational level of household (Education), expressed as the number of years of education received by the head of the household; (4) Health status of household (Health), 1 to 5 are excellent, good, medium, poor, and incapable of labor, respectively; (5) Whether the household has a professional training in agriculture (Train), assigned a value of 1 when the respondent has participated in vocational training, and 0 vice versa; (6) Area of land under cultivation operated by households at the beginning of the year (Farmland), the area of cultivated land owned by the household at the beginning of the year; (7) Number of family laborers (Family labor); (8) Family's total annual income (Income), is the sum of the household's income in a year, which is taken as the natural logarithm in this paper; (9) Whether the family is a party member household (Party), assigned a value of 1 when the respondent's household is a party member household, and vice versa; (10) Whether the household has access to the Internet (Internet), assigned a value of 1 when the household has access to information on the Internet, and 0 otherwise.…”
Section: Control Variablesmentioning
confidence: 99%
“…This aligns with the findings of prior research that have examined poverty and its determinants. For example, Li et al [15] found that vulnerabilities related to climate change, living habits, and medical accessibility were positively associated with health poverty among rice farmers in China. Khan et al [16] highlighted the financial risks and potential poverty resulting from large and unpredictable health payments in Bangladesh.…”
Section: Reproductive Health Characteristicsmentioning
confidence: 99%
“…Over the past decade, the disparity in employment opportunities, medical services, and household income for those in rural areas [12][13][14][15] has led to a migration of male farmers-particularly young and middle-aged-seeking improved employment opportunities and higher income. These in-migration dynamics strain women left in rural areas who must simultaneously provide for household public goods (e.g., caring for the elders and children) while working more frequently in agricultural production.…”
Section: Rural Women In Farmingmentioning
confidence: 99%